Linguistic Decision Making Numerical Scale Model and Consistency-Driven Methodology - Dong, Yucheng; Xu, Jiuping; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book proposes a novel CWW model to personalize individual semantics in linguistic decision making, based on two new concepts: numerical scale and consistency-driven methodology. The numerical scale model provides a unified framework to connect different linguistic symbolic computational models for CWW, and the consistency-driven methodology customizes individuals' semantics to support linguistic group decision making by setting personalized numerical scales. The book is a valuable resource for researchers and postgraduates who are interested in CWW in linguistic decision making.
1 Introduction -- 2 Numerical Scale Model -- 3 A Unified Framework -- 4 Consistency of Interval-Like Reciprocal Preference Relations -- 5 Consistency-Driven Methodology -- 6 Applications in Various Decision Problems.
Keywords: Semiotics; Psycholinguistics; Semiotics; Psycholinguistics and Cognitive Lingusitics